Підвищення витривалості студентів засобами скандинавської ходьби на заняттях фізичного виховання - Азаренкова, Любов Леонідівна (Національний педагогічний університет ім. М. П. Драгоманова, 2021)
У роботі проаналізовано вплив скандинавської ходьби на здоров’я студентів в процесі занять фізичним вихованням. Визначено актуальність аеробних вправ для підвищення працездатності студентів. Оцінено рівень витривалості студентів 1 курсів загальної основної медичної групи за індексом витривалості Т. Круцевич. Представлена програма занять зі скандинавської ходьби для підвищення рівня витривалості студентів, яка розраховувалась на 16 тижнів практичних занять з розрахунку 2 рази на тиждень. Також програма включала в себе теоретичний матеріал з основ техніки пересування зі скандинавської ходьби, презентацію о користі скандинавської ходьби на організм людини. Для більш ефективного впливу на організм людини навантаження було розподілено зростаючою динамікою на протязі 16 тижнів. За результатами тестування було визначено позитивний вплив на рівень витривалості студентів.

Modern students spend a large amount of time sitting, and with the introduction of distance learning students have to study constantly on the computer, which greatly reduces the level of physical activity. Therefore it is important to introduce new forms and means of physical training, dosed for the volume and intensity of cyclic exercise, which are used in aerobic mode, contributing to the increase in physical activity, the gradual development of global vitality. The work has analyzed the impact of Nordic walking on the health of students in the process of physical education. The literary sources indicated that the students can improve the functional state of the musculoskeletal apparatus and cardiorespiratory system by exercising with Nordic walking. Classes Nordic walking reduces the strain on the knee joints and spine, strengthens the muscles of the back and neck, raise the level of vitality and immunity, form and maintain the correct posture. Classes Nordic walking positively influence the status of the respiratory system, because the exercise takes place on a fresh stomach, so the body receives a large amount of acid. The relevance of aerobic activities for increasing the productivity of students has been determined. Estimated the level of vitality of the students of the 1st year of the general basic medical group by the index of vitality T. Krutsevich. To increase the knowledge of Nordic walking and the level of vitality students were asked to take part in the program. The goal of the program is to formulate theoretical knowledge of the students about the effective effect of Nordic Walking and to increase the students' level of vitality by means of Nordic Walking. Presented program of activities for Nordic walking to raise the level of vitality students counted for 16 months of practical exercises for the rate of 2 times per day. The program also included theoretical material on the basics of Nordic walking techniques, a presentation on the correlation of Nordic walking to the human body. For a more effective impact on the human body the pressure was distributed by the growing dynamics during 16 days. According to the results of the test the positive effect of Nordic walking on the level of vitality of the students was determined.
Increasing students' endurance by means of Nordic walking in physical education classes
Keywords: скандинавська ходьба; студенти; рівень; витривалість; програма; Nordic walking; students; level; endurance; program